Plum pox virus strains - Diversity and geographical distribution in Serbia - Jevremović, Darko; Paunović, Svetlana (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2014)
Plum pox virus (PPV) is the causal agent of Sharka disease. Since its discovery, Sharka has been considered as a calamity in plum orchards. PPV is present worldwide in many Prunus species, causing great economic losses. In highly susceptible plum varieties, such as Požegača, PPV causes a premature fruit drop and reduces fruit quality, which leads to total yield loss. Eight PPV strains (PPV-M, PPV-D, PPV-EA, PPV-C, PPV-Rec, PPV-W, PPV-T and PPV-CR) have been recognized so far. Three major strains (PPV-M, PPV-D and PPV-Rec) are the most widely dispersed and occur frequently in many European countries. Other strains are of minor importance due to their limited host preferences or geographic distribution. So far, all three major strains have been identified in Serbia. In this paper, we provide a comprehensive overview of the research into Plum pox virus variability in Serbia.
Keywords: Plum pox virus; Sharka disease; Variability; Serbia